The Implementation of Structural Equation Modeling (SEM) on Academic Ability and Family Environment in Twelfth-Grade Students' Selecting of Public Universities - Taena, Vinsensia Gerosa; Simarmata, Justin Eduardo; Delvion, Eduardus Beo Seso (Jurusan Matematika, Fakultas Teknik, Universitas Bangka Belitung, 2025)
Public universities are the primary institutions chosen by students who have recently completed their secondary education to continue their studies. This decision is influenced by both internal and external factors. Several factors that affect the decision to pursue further education at a public university include academic ability and the family environment. The aim of this study is to identify the structural model between these variables using the Structural Equation Modeling (SEM) method. The data for this study were collected from 203 twelfth-grade students of Taekas Public High School in the 2023/2024 academic year. The analysis results indicate that the influence of the latent variable of academic ability on the interest in selecting a public university, based on the path coefficient value, is 0.68. This implies that the better the student's academic ability, the greater their interest in selecting a public university. The influence of the latent variable of family environment on the interest in selecting a public university, based on the path coefficient value, is 0.78. This suggests that the better the student's family environment, the greater their interest in selecting a public university.